Summary of the seismic and volcanic activity in Costa Rica during 2011 - Barquero, Rafael (2011)
In 2011 the National Seismological Network (RSN) recorded over 2000 earthquakes den-tro the country (Fig. 1) of which 96 were reported felt by the people of Costa Rica, activity lower than that of 2010, year they were reported 111 events senses.